The role of hypoxia in controlling Volatagegated Sodium Channels (VGSCS) induced breast cancer invasiveness - Makhtar, Noor Fatmawati (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
This study was designed mainly to investigate the role of transcription factor, hypoxia inducible factor- 1a (HIF -1a) in enhancing Nav1.5 and nNav1.5 expression in breast cancer that transforms it to become aggressive. siRNA was conducted to knockdown HIF -1 a expression in the aggressive MDAMB- 231 cells whilst hypoxia-mimetic agent. cobalt chloride (CoCI 2) was used to stabilize HIF-1a in the less aggressive MCF-7 cells . Total RNA and protein were extracted and subjected to real-time PCR and Western blotting . Migration and motility assays were carried out to study effect of treatments (siRNA and CoCI2) on metastatic cell behaviours. Nav1 .5 , nNav1 .5, HIF-1a and CA9 expression were all hiqhlv expressed in MDA-MB-231 cells . siRNA caused a siqnificant decreased in HIF -1 a expression (mRNA and protein) and HIF-1 a-common target gene. CA9. mRNA expression of Nav1 .5 but not nNav1.5 was significantly downregulated by siRNA-HIF-1a followed by suppression of migration. When MCF-7 cells were treated with CoCI2 , HIF-1a protein, CA9 and Nav1.5mRNA expression was increased significantly but not nNav1 .5 followed by enhanced motility and migration. In conclusion. transcription factor, HIF-1a able to regulate Nav1 .5 (but not nNav1.5) in breast cancer to promote its aggressiveness.